Dynamics of Participatory Culture in Elections: From Tudang Sipulung Culture to Open Discussion and the Phenomenon of Money Politics - Aurelia, Firzah; Idrus, Idham Irwansyah; Suhaeb, Fridaus W. (Jurnal Multidisiplin Madani, 2024)
Active community participation in the election process is very important in guarding this democratic party. Of course there is dynamics in this participation. Apart from that, the transformation of the tudang sipulung culture towards open discussion and the phenomenon of money politics are part of the dynamics of active community participation in this election process. This research uses descriptive qualitative methods with the aim of explaining the transformation of tudang sipulung culture into open discussion, the phenomenon of money politics and the dynamics of participatory culture in elections